ANALISIS PENGARUH PELAKSANAAN SISTEM PENAGIHAN AKTIF TERHADAP TINGKAT PENCAIRAN TUNGGAKAN WAJIB PAJAK ORANG PRIBADI PADA KANTOR PELAYANAN PAJAK PRATAMA MANADO - Alumu, Sumaryani Ode; Alexander, Stanly W.; Pangerapan, Sonny (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Tax is a very potential alternative in order to raise the fund. Based on that, then increased public awareness in this regard should be supported with an increase in the taxation of an active role in gonverment to improve people’s welfare and encoraging people to take responsiblity and play o role in the development of economic development. The purpose of this research is to know whether exist or not the influence of activated the billing system on taxpayer’s. The research methode used simple linear regression analysis and for data was processed using SPSS V.17, The results showed that the relationship between the active billing with the level of tax arrears of individual taxpayer’s in the Tax Office Primary  Manado no significant effect and classified as ineffective with the value of correlation Pearson of letter warning of -.299 and a letter of force of -370, while the contributions given billing active of delinquent disbursement personal taxpayer’s is 18,3%, the rest of it is 81,7%, disbursement of tax is affected by other which are not examined in this research.Keywords : Active Billing Implementation, Disbursement of Tax Arrears